Connecting Provider to home: A home‐based social intervention program for older adults. Issue 6 (12th March 2021) - Moreno, Gerardo; Mangione, Carol M.; Tseng, Chi‐Hong; Weir, Melanie; Loza, Rosaneli; Desai, Lisa; Grotts, Jonathan; Gelb, Eve
Abstract: Objective: Patients with multiple medical conditions and complex social issues are at risk for high utilization and poor outcomes. The Connecting Provider to Home program deployed teams of a social worker and a community health worker (CHW) to support patients with social issues and access to primary care. Our objectives were to examine the impact of the program on utilization and satisfaction with care among older adults with complex social and medical issues. Design: Retrospective quasi‐experimental observational study with matched comparator group. Setting: Community‐based program in Southern California. Participants: Four hundred twenty community dwelling adults. Intervention: Community‐based healthcare program delivered by a social worker and CHW team for older adults with complex medical and social needs. Measurements: Acute hospitalization and emergency department (ED) visits in the 12 months preceding and following enrollment in the pilot program. A "difference‐in‐difference" analysis using a matched comparator group was conducted. Comparator group data of patients receiving usual care were obtained. Surveys were conducted to assess patient satisfaction and experiences with the program. Results: The mean age of patients was 74 years, and the program demonstrated statistically significant reductions in acute hospitalizations and ED use compared with 700 comparator patients. Pre/post‐acute hospitalizations and ED visits were reduced in the intervention group. The average per patient per year reduction in acute hospitalizations was −0.66, whereas the average per patient reduction in ED use was −0.57. Patients enrolled in the program reported high levels of satisfaction and rated the program favorably. Conclusions: A care model with a social worker and CHW can be linked to primary care to address patient social needs and potentially reduce utilization of healthcare services and enhance patient experiences with care. Abstract : See related editorial by Danto‐Nocton et al . and article by Robinson et al . in this issue.